2020
DOI: 10.11591/ijere.v9i3.20594
|View full text |Cite
|
Sign up to set email alerts
|

Modification level and test of scientific argumentation skill: Development and validity

Abstract: This study focuses on developing the new level of scientific argumentation skills and new items that are feasible and valid for used. There are 195 science students at Islamic State School 1 (MAN 1) Yogyakarta as participant in this study. Random sampling technique was used from the three schools of Islamis State School (MAN) in Yogyakarta, Indonesia. There are seven experts (3 Professor, 2 teachers, and 2 graduate students) reviewed 14 items for the first phase of this study. For the second phase, 98 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…This study was in line with research by Ping (2020), which provides significant improvement in argumentation and science process skills of biology who experience the MADI approach in practical biology. The subsequent research that is in line with the current research is carried out by Perdana et al (2020). The difference is that previous studies researched biology subjects, so this study was conducted to measure the effect of students' science process skills on students' argumentation skills in physics subjects with elasticity and Hooke's law.…”
Section: Introductionmentioning
confidence: 82%
“…This study was in line with research by Ping (2020), which provides significant improvement in argumentation and science process skills of biology who experience the MADI approach in practical biology. The subsequent research that is in line with the current research is carried out by Perdana et al (2020). The difference is that previous studies researched biology subjects, so this study was conducted to measure the effect of students' science process skills on students' argumentation skills in physics subjects with elasticity and Hooke's law.…”
Section: Introductionmentioning
confidence: 82%
“…Based on the the level of scientific argumentation or 21st century skill, the sample choosed was MAN 1 because from perevious study [21], they had low level of scientific argumentation skill. In MAN 1 Yogyakarta, the class was chosed based on the material in the Indonesia Curriculum (K13).…”
Section: Research Methods 21 Model Of Researchmentioning
confidence: 99%
“…All matrices have been validated by experts; 2) Guidelines for teachers which consist of lesson plans. This serves as a guide for teachers to convey the students with different approaches to each class; 3) Learning Materials which are modules developed by researchers; 4) Instruments to test the ability of scientific argumentation include open tests [21]. Assessment of student skills based on the rubric 0-5.…”
Section: Methodsmentioning
confidence: 99%
“…Research about argumentation has shown that students have naïve argumentation components (Driver et al, 2000) and thus poor argumentation skills (Perdana et al, 2019). They seem to lack the knowledge of the argumentation reasoning skills (Berland & Reiser, 2009; Erduran et al, 2004).…”
Section: Argumentationmentioning
confidence: 99%